2019
DOI: 10.12955/cbup.v7.1471
|View full text |Cite
|
Sign up to set email alerts
|

Influenсe of Seasonal Factor on the Chemical Composition of Persimmon

Abstract: Persimmon is one of the most popular and favorite fruits not only in Georgia, but also in other countries. People love it for its unique specific taste and high nutritional value. There are more than 500 types of persimmon, properties and tastes which depend on the persimmon growing conditions. The purpose of this project was to study the persimmon fruit chemical composition, the regularity in the quantity changes of the bioactive substances and technical-economical persimmon parameters during its storage and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…Yaqub et al (2016) reported fruit sugariness of 12.5% in Pakistani persimmons, which is comparable to Ukrainian cultivars. In contrast, sugar contents in Georgian fruit ranged from 13.0% to 19.1% (Bejanidze et al 2019), and the sugar content in Turkish fruit was recorded as 16.3% (Altuntas et al 2011) and 14.6% (Candir et al 2009). The titrated acids content in Ukrainian persimmon ranged from 0.12% to 0.32% (Table ).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…Yaqub et al (2016) reported fruit sugariness of 12.5% in Pakistani persimmons, which is comparable to Ukrainian cultivars. In contrast, sugar contents in Georgian fruit ranged from 13.0% to 19.1% (Bejanidze et al 2019), and the sugar content in Turkish fruit was recorded as 16.3% (Altuntas et al 2011) and 14.6% (Candir et al 2009). The titrated acids content in Ukrainian persimmon ranged from 0.12% to 0.32% (Table ).…”
Section: Resultsmentioning
confidence: 83%
“…The titrated acids content in Ukrainian persimmon ranged from 0.12% to 0.32% (Table ). Baltacioğlu and Artik (2013), recorded that the content of titrated acids in persimmon fruits produced in Turkey ranged from 0.28% to 0.46%, while in Georgia, the titrated acid contents ranged from 0.05% to 0.18% (Bejanidze et al 2019).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation